Egg Supplementation and Dietary Intake Variability During Cytotoxic Chemotherapy Cycles of Breast Cancer Patients - Akhtar, Khursheda; Arefin, Saidul; Kawser, Mahbuba; Sham, Fahmida Faizha; Islam, Sheikh Nazrul (Journal of Preventive and Social Medicine, 2025)
Background: The variability in dietary intake during chemotherapy, coupled with the adverse effects of cytotoxic agents, highlights the critical need for targeted nutritional strategies to mitigate malnutrition and support recovery. This study aims to assess dietary intake variability among breast cancer patients undergoing cytotoxic chemotherapy with egg supplementation. Methods: The study was conducted among breast cancer patients receiving chemotherapy at the National Institute of Cancer Research and Hospital (NICRH) from December 2022 to November 2023. Fifty-two patients were enrolled in each group (control and experimental). The experimental group received a supplementation of three eggs (one whole egg and white portion of two eggs). Nutritional status was assessed using the 7-point Subjective Global Assessment (SGA) tool, classifying patients as well-nourished or moderately to severely malnourished. Dietary intake was evaluated using a 7-day food frequency questionnaire. Results: The intervention group showed significant improvements in dietary habits and health outcomes compared to the control group. Rice intake was higher in the intervention group (90.3% vs. 78.8%), and they consumed more roti (59.6% vs. 40.4%). Egg consumption increased to 100% in the experimental group, while the control group showed no change. Milk intake also increased in the intervention group (80.7% vs. 73.1%). Vegetable intake improved in both groups, with the experimental group increasing from 40.4% to 59.6%, while the control group saw a larger increase (21.2% to 76.9%). Fruit intake increased in the intervention group (78.8% to 84.5%) but decreased in the control group. The intervention group consumed significantly more egg protein (20.07 g vs. 12.53 g, p<0.001). The intervention group effectively mitigated weight loss over time, with 76.9% maintaining no weight loss at the end line compared to only 32.7% in the control group (p < 0.05) and better food habits and fewer GI symptoms compared to the control group. Conclusion: Egg supplementation significantly increased egg protein intake in the experimental group, but overall dietary intake remained inadequate, highlighting the need for comprehensive nutritional interventions addressing barriers such as taste changes, gastrointestinal symptoms, and fatigue to improve nutritional status and quality of life for chemotherapy patients. JOPSOM 2024; 43(2): 17-28